Analysis of NFT (Non-Fungible Tokens) In Relation to Money Laundering - Amin Sadiqin (Lafadz Jaya Publisher, 2023)
In the development of information and communication technology, there are many developments that occur. One of them is the emergence of NFTs as the latest trend in digital trading. This, of course, is a new breakthrough in the digital world. However, this can also be a loophole in committing money laundering crimes. In this research, we are using a qualitative descriptive approach with analytical methods. The result of this analysis is thatThe main problem with money laundering via NFTs and cryptocurrencies is the lack of understanding of the role of cryptocurrencies in financial crimes. As long as this misunderstanding is not addressed, the potential for the use of NFTs as a new method of financial crime will increase sharply to the point of endangering national security.